9. OUTCOMES OF PATIENT CARE AFTER OPEN-HEART SURGERY AT THE CARDIOVASCULAR INSTITUTE OF 108 MILITARY CENTRAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the outcomes of patient care after open-heart surgery at the Cardiovascular Institute, 108 Military Central Hospital in 2025.Methods: A prospective descriptive study.Results: The average duration of postoperative drainage was 2.6 ± 1.3 days; mean mechanical ventilation time was 13.7 ± 32.0 hours; and ICU stay averaged 2.7 ± 3.3 days. Catheter and urinary catheter retention times were 3.6 ± 2.0 days and 3.3 ± 2.4 days, respectively. Most patients (94.4%) started early mobilization within the first 12–24 hours postoperatively.Conclusion: Postoperative care after open-heart surgery at the 108 Military Central Hospital was effective, with a low complication rate; patients recovered early and reported high satisfaction with the care received.
Keywords: Postoperative care; open-heart surgery; postoperative complications; patient recovery.